Quantitation of pregabalin by pre-column derivatization HPLC with UV detection - Mutalabisin, Muhammad Fathiy; Chatterjee, Bappaditya (2018)
Introduction: Pregabalin, a drug used to treat neuropathic pain, cannot be detected in its original form by simple high performance liquid chromatography (HPLC) with UV or fluorescence detector due to absence of chromophore group. Objective: To develop and validate a HPLC method with UV detection by pre-column derivatization reaction.